Estimation of the cost of Taenia solium cysticercosis in eastern Cape Province, South Africa - Carabin, H.; Krecek, R.C.; Cowan, L.D.; Michael, L.; Foyaca-Sibat, H.; Nash, T.; Willingham, Arve Lee (Wiley, 2006)
This paper provides a comprehensive estimate of the societal costs of Taenia solium cysticercosis for the Eastern Cape Province (ECP), South Africa, as an objective measure of its impact in this endemic area. Epidemiological data on the prevalence of epilepsy, proportion of epilepsy cases due to neurocysticercosis (NCC) and consequences of cysticercosis were gathered from published and unpublished sources. Economical data were mostly obtained from governmental sources. Three methods were used for estimating productivity losses. Monte Carlo sampling was used to represent the uncertainty of the estimates with 95% Credible Intervals (95% CI). The estimation is for 1 year using a societal approach. All costs are reported in 2004 US$. Results Overall, there were an estimated 34 662 (95% CI: 17 167–54 068) NCC-associated cases of epilepsy in ECP in 2004. The overall monetary burden (in million of US$) was estimated to vary from US$18.6 (95% CI: US$9.0–32.9) to US$34.2 (95% CI: US$12.8–70.0) depending on the method used to estimate productivity losses. The agricultural sector contributed an average of $5.0 million. The prevalence of epilepsy, proportion of productivity reduction and the proportion of epilepsy cases attributable to NCC had the largest impact on the overall estimates. This preliminary estimate suggests that T. solium cysticercosis results in considerable monetary costs to a region that is already economically constrained. Because this infection is preventable, these results could guide stakeholders in deciding where to invest scarce health and agricultural resources in their countries.